Electrochemical sensors based on biomimetic magnetic molecularly imprinted polymer for selective quantification of methyl green in environmental samples - Khan, Sabir (2019)
A new biomimetic sensor was prepared on carbon paste with magnetic molecularly imprinted polymer (mag-MIP)for sensitive and selective detection of methyl green dye. The mag-MIP was synthesized using a functional monomer that was selected before by computational simulation. A mag-NIP (magnetic non-imprinted polymer)control material was also prepared for comparative purposes. Modeling adsorption studied revealed that the dye-polymer interface followed pseudo-first order kinetics and that maximum adsorption (Qm)of the dye on mag-MIP was 3.13 mg g−1, while the value for mag-NIP was 1.58 mg g−1. The selective material was used as a sensing spot in fabrication of an electrochemical sensor based on modified carbon paste. For electrochemical analysis, the best achievement of the sensor was acquire by tack together a paste with 6.7% (w/w)of mag-MIP and using square-wave adsorptive anodic stripping voltammetry (SWAdASV)in 0.1 mol L−1 phosphate buffer (pH 7.0), with an applied potential (Eappl)of 0.3 V vs. Ag|AgClsat during an adsorption time (Tads)of 120 s. The results were obtained under optimized conditions in which sensor provided a linear concentration range of methyl green from 9.9 × 10−8 to 1.8 × 10−6 mol L−1, with a limit of detection (LOD)of 1.0 × 10−8 mol L−1 and a satisfactory relative standard deviation (RSD)of 4.3% (n = 15). The proposed sensor was applying using two spiked river water samples, obtaining recoveries ranging from 93% to 103%. The proposed method exhibits excellent precision also high reliability and proved to be an alternative method for the quantification of methyl green in real samples.